Pelanggaran Hak Asasi Manusia: Pintu Masuk Pasukan Internasional ke Papua - Aris Sarjito (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This research explores human rights violations in Papua, focusing on the feasibility of international troop deployment as an intervention strategy against a backdrop of severe abuses such as extrajudicial killings and arbitrary arrests documented by organizations such as Amnesty International. The study aims to assess the potential role of international troops in safeguarding human rights and maintaining peace, using a qualitative methodology to analyze secondary data from human rights organizations and governmental sources to identify trends and challenges. The main contributions include highlighting gaps in existing interventions, proposing a conceptual framework for international troop deployment that considers legal, political, and ethical dimensions, and contextualizing issues of state sovereignty and regional diplomacy within the ASEAN framework. Specific findings indicate that while international troop deployment could enhance civilian protection and accountability, it faces significant barriers, including legal constraints related to international law, political resistance from local authorities and neighboring states, and ethical concerns such as the risk of escalating violence and undermining local governance. The study concludes by suggesting a balanced approach emphasizing dialogue, sustainable development, and cooperation within ASEAN to address human rights issues in Papua effectively.